SYECH SULTAN MARUHUM ALAM SYAH SEBAGAI TOKOH AGAMA DI DESA TANJUNG ALAI KECAMATAN LUBUK PINANG KABUPATEN MUKOMUKO TAHUN (1982-2012) - annggaraini, Weni Norita; Kaksim, Kaksim; Yulia, Refni (Pendidikan Sejarah, 2014)
This thesis discussed about Syech Sultan Maruhum Alamsyah in developing the teaching of Islam in the village of Tanjung Pinang Alai District of Lubuk Mukomuko regency .The goals are the people around the village of Tanjung Alai and more understand about the teaching of Islam and practice it . Syech Sultan Maruhum Alamsyah lead in the recitation not only think about of Moeslim people at this point but also think about how the state of Muslims after Syech Sultan Maruhum Alamsyah died especially in the teaching of Islam . In this caseÂ  Syech Sultan Maruhum Alamsyah gives the opportunity for students who seriously to recognize science and Syech Sultan Maruhum AlamsyahÂ  itself . The results of the research above it can be concluded that the Syech Sultan MaruhumÂ  Alamsyah who a religious leader in the village of Tanjung Alai that convey the message of Islam through recitation of th Qurâan that done in Nurul Yakin mosque in the village of Tanjung Alai Kecamatan Lubuk Pinang Mukomuko regency . Syech Sultan MaruhumÂ  Alamsyah hope thatÂ  to establish Nurul Yakin mosque and do the tarekat or Suluk in the village of Tanjung Alai , it can change behavior the people, especially Tanjung Alai people